Analisis Usability dan Redesign Aplikasi Seluler Dengan Metode User-Centered Design (Studi Kasus Starbucks Indonesia) - Carmeline, Benedicta Christina; Kamal, Irsyad (Journal of Digital Business Innovation, 2023)
Sales of processed coffee products in Indonesia are increasing along with the growth of coffee outlets and national consumption. Starbucks is trying to expand its services through a mobile application, but the usability of the application is still not optimal with user interface (UI) and user experience (UX) that have not satisfied users. Therefore, this study aims to improve usability through redesign using the user-centered design (UCD) method, which is based on constraints and feedback identified from users through initial surveys and interviews. The obstacles faced by users include unattractive appearance, poorly understood flow, and features that are difficult to find. The results of the redesign were compared with the current application design based on usability testing scores, average system usability scale (SUS) scores, and user satisfaction. The results of the usability testing and SUS scale showed a significant improvement from 46 to 69 and 55 to 89, indicating that the redesign has successfully improved the usability of the Starbucks Indonesia mobile application in accordance with the research objectives.